Rise and fall of the constitutionalism of Cádiz - Jorge Pérez Alonso (Estudios de Deusto, 2014)
This article performs a critical analysis of the book authored by Professor Joaquín Varela Suanzes-Carpegna entitled La monarquía doceañista (1810-1837). Avatares, encomios y denuestos de una extraña forma de gobierno Marcial Pons, 2013. Published online: 25 November 2014